Analisis Penerapan Pembelajaran Diferensiasi Mata Pelajaran Biologi Di SMA Negeri 6 Metro: (Analysis of the implementation of differentiation learning in biology subjects at sma negeri 6 metro) - Hasanah, Dara Fatikha Sabila; Hayati, Dwi Kurnia (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
Differentiated learning allows educators to meet the learning needs of each student, such as interests, learning profiles, and student readiness in order to obtain optimal learning outcomes. The aim of this research was to describe the process of implementing differentiated learning in Biology subjects in class X Science. This research is qualitative research with the presentation of descriptive data such as writing, words and behavior that needs to be seen. This research was carried out in class X students at SMA N6 Metro. Research information was obtained from teachers as subjects and class X science students as objects. The differentiated learning implemented in class X at SMAN 6 Metro has had a positive impact on students and teachers. The differentiated learning that is applied is differentiated processes and products. Data collection techniques in this research are through interviews, document study and observation. The research results obtained state that the application of differentiated learning in driving schools in Metro City can be carried out through project learning or P5. Key words: Differentiated learning, needs, student activity. abstrak. Pembelajaran berdiferensiasi memungkinkan pendidik untuk memenuhi kebutuhan belajar tiap peserta didik, seperti minat, profil belajar, dan kesiapan peserta didik supaya memperoleh hasil belajar optimal. Tujuan dilaksanakan penelitian ini guna mendeskripsikan proses penerapan pembelajaran berdiferensiasi mata pelajaran Biologi di kelas X IPA. Penelitian ini merupakan penelitian kualitatif dengan penyajian data deskriptif seperti tulisan, perkataan dan perilaku yang perlu dilihat. Penelitian ini diaksanakan dipeserta didik kelas X SMA N6 Metro. Informasi penelitian diperoleh dari guru sebagai subjek dan peserta didik kelas X IPA sebagai objek. Pembelajaran berdiferensiasi yang diterapkan di kelas X SMAN 6 Metro memberikan dampak positif untuk peserta didik dan guru. Pembelajaran berdiferensiasi yang diterapkan yaitu berdiferensiasi proses dan produk. Teknik pengumpulan data dalam penellitian ini melalui wawancara, studi dokumen dan observasi. Hasil penelitian yang didapatkan menyatakan bahwa penerapan pembelajaran berdiferensiasi di sekolah penggerak di Kota Metro bisa dilangsungkan melalui pembelajaran proyek atau P5. Kata kunci: Pembelajaran berdiferensiasi,kebutuhan,keaktifan peserta didik.